1999
DOI: 10.1021/ac990664v
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Postcolumn Addition of 2-(2-Methoxyethoxy)ethanol, a Signal-Enhancing Modifier, for Metabolite Screening with Liquid Chromatography and Negative Ion Electrospray Ionization Mass Spectrometry

Abstract: A strategy for highly sensitive metabolite screening by liquid chromatography-electrospray ionization (ESI) mass spectrometry with the negative-ion mode that involves the use of a reversed-phase column in gradient-elution mode and postcolumn addition of 2-(2-methoxyethoxy)ethanol (2-MEE), a novel signal-enhancing modifier, has been described. When a mobile phase of 50 mM ammonium acetate/acetic acid buffer (pH 4.4) at a flow rate of 100 microL/min was employed, poor ESI response of ibuprofen as a model drug, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The poor ionization efficiency may have been due to both the high surface tension of the mobile phase and the ion-suppression effect of the acetate anion in the mobile phase. Post column addition of 2-(2-methoxyethoxy)ethanol (50 L/min) increased the signal of analyte approximately 100-fold [99] and dramatically improved the ESI responses of all urinary metabolites as well. This method was also used to enhance the signal of rat urinary and biliary metabolites for a novel antirheumatic drug esonarimod [100].…”
Section: Ion-pairing Reagents and Post-column Additionmentioning
confidence: 99%
“…The poor ionization efficiency may have been due to both the high surface tension of the mobile phase and the ion-suppression effect of the acetate anion in the mobile phase. Post column addition of 2-(2-methoxyethoxy)ethanol (50 L/min) increased the signal of analyte approximately 100-fold [99] and dramatically improved the ESI responses of all urinary metabolites as well. This method was also used to enhance the signal of rat urinary and biliary metabolites for a novel antirheumatic drug esonarimod [100].…”
Section: Ion-pairing Reagents and Post-column Additionmentioning
confidence: 99%
“…32 Similarly, Yamaguchi et al reported a 100-fold improvement in sensitivity for ions formed from solutions containing ammonium acetate and acetic acid, by addition of the low vapor pressure solvent 2-(2-methoxyethoxy)ethanol (2-MEE; bp 193 °C). 33 The authors speculated that "the ion-suppression effect of acetate ion" is responsible in part for the poor ESI response obtained from ammonium acetate/acetic acid-containing solutions and that 2-MEE counteracts signal suppression by allowing acetic acid and water to preferentially evaporate from the electrospray droplets prior to ion formation. 33 Here, we report that both the abundance and the reproducibility of ion signal of cytochrome c and ubiquitin ions formed by nanoES from aqueous solutions containing 0 or 2.0 × 10 −2 M sodium chloride are significantly improved by adding 7 or 8 M ammonium acetate to electrospray solutions.…”
mentioning
confidence: 99%
“…33 The authors speculated that "the ion-suppression effect of acetate ion" is responsible in part for the poor ESI response obtained from ammonium acetate/acetic acid-containing solutions and that 2-MEE counteracts signal suppression by allowing acetic acid and water to preferentially evaporate from the electrospray droplets prior to ion formation. 33 Here, we report that both the abundance and the reproducibility of ion signal of cytochrome c and ubiquitin ions formed by nanoES from aqueous solutions containing 0 or 2.0 × 10 −2 M sodium chloride are significantly improved by adding 7 or 8 M ammonium acetate to electrospray solutions. We propose that this effect is due to the removal of Na + and Cl − from solution by precipitation within the evaporating electrospray droplets prior to the formation of gas-phase protein ions.…”
mentioning
confidence: 99%
“…In addition, as a typical feature of the negative ion detection mode, only a low background occurred and therefore, excellent and easily interpretable mass spectra were obtained with both, ESI and APCI. As a typical example of a sulfonated aromatic compound, Figure 7 shows the APCI mass spectrum of Crocein Orange G. It is worth mentioning that post-column addition of 2-(2-methoxyethoxy)ethanol proved to exert a beneficial influence on signal intensities, as first published by Yamaguchi et al [24].…”
Section: As Impressively Illustrated Inmentioning
confidence: 79%